1993
DOI: 10.1007/bf02505764
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of interaction of disopyramide with the cardiac sodium channel: Fast dissociation from open channels at normal rest potentials

Abstract: Block of cardiac sodium channels is enhanced by repetitive depolarization. It is not clear whether the changes in drug binding result from a change in affinity that is dependent on voltage or on the actual state of the channel. This question was examined in rabbit ventricular myocytes by analyzing the kinetics of block of single sodium channel currents with normal gating kinetics or channels with inactivation and deactivation slowed by pyrethrin toxins. At -20 and -40 mV, disopyramide 100 microM blocked the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
(69 reference statements)
2
9
0
Order By: Relevance
“…The early inward current was greatly increased (Fig. 6c), with a relatively large amplitude and fast kinetics consistent with pyrethroid-modified I Na (Grant et al, 1993;Spencer et al, 2001). Importantly, in all myocytes examined, the pyrethroid-sensitive current included de novo, a persistent inward current (Fig.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The early inward current was greatly increased (Fig. 6c), with a relatively large amplitude and fast kinetics consistent with pyrethroid-modified I Na (Grant et al, 1993;Spencer et al, 2001). Importantly, in all myocytes examined, the pyrethroid-sensitive current included de novo, a persistent inward current (Fig.…”
supporting
confidence: 66%
“…This action underlies the neurotoxic basis for sensorimotor changes typical of pyrethroid effects in both vertebrates and invertebrates (de Weille et al, 1990;Tabarean and Narahashi, 1998;Vais et al, 2000). In addition, these agents may produce cardiotoxic effects mediated by I Na prolongation in cardiac myocytes (Grant et al, 1993;Spencer et al, 2001). Since global use of pyrethroids has increased, especially in regions burdened by arthropod-borne diseases, a consequent rise in acute pyrethroid exposures in humans demands a more complete understanding of their mode of action (Gupta et al, 2003;Habtewold et al, 2004).…”
mentioning
confidence: 99%
“…This is an example of use-dependent unblocking (35). A Prior studies from this laboratory have shown that disopyramide blocks normal open sodium channels and those in which the inactivation process has been slowed or removed (19). The influence of 50 ,gM disopyramide on single sodium channels with inactivation removed by deltamethrin was examined at external sodium concentrations of 120 and 180 mM.…”
Section: Methodsmentioning
confidence: 99%
“…We conclude that the influence of the permeant ion concentration on the blocking action of antiarrhythmic drugs may depend importantly on their blocking mechanism. Some of these results have been communicated in abstract form ( 19,25).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation